(untitled) (Medico Legal Update, 2023)
The uniqueness of human fingerprint plays the most prominent role in forensic investigation as a physical evidence Which is useful for criminal identification. With its unique features no two fingerprints have ever been found to be identical. In legal cases the identification of such print established the relationship between crime scene and the culprit. Generally , there are three types of fingerprint is to be found visible print, plastic print and latent print ( invisible print) which has been taken in account for identification. There is no such crucial method is used for decipher the visible print and plastic print because they are easily visible to naked eye but in case of latent print the process for enhancement is necessary for the latent fingerprint to be observed by naked eye. The most encountered fingerprint is the latent fingerprint which is unconsciously left by perpetrators at any surface. For visualizing such prints Various method have been reported for the development of latent fingerprint on different surfaces. This present study introducing a new visualizing agent for the development of latent fingerprint by using Carbon Powder on various non-porous & porous surface through the powdering method. Here we use candle flame to collect black carbon mass and turn it into powder which is used for obtaining latent fingerprints. By the application of these powder it is observed that it gives a clear ridge on various surfaces.